"Blurring the Line": Intoxication, Gender, Consent, and Sexual Encounters Among Young Adults. (March 2022) - Hunt, Geoffrey; Sanders, Emile; Petersen, Margit Anne; Bogren, Alexandra
Social concern about sexual practices and sexual consent among young adults has increased significantly in recent years, and intoxication has often played a key role in such debates. While many studies have long suggested that alcohol plays a role in facilitating (casual) sexual encounters, intoxication has largely either been conceptualized as a risk factor, or researchers have focused on the pharmacological effects of alcohol on behaviors associated with sexual interaction and consent. To date little work has explored how young adults define and negotiate acceptable and unacceptable levels of intoxication during sexual encounters, nor the ways in which different levels of intoxication influence gendered sexual scripts and meanings of consent. This paper explores the latter two research questions using data from 145 in-depth, qualitative interviews with cisgender, heterosexual young adults ages 18–25 in the San Francisco Bay Area. In examining these interview data, by exploring the relationship between intoxication and sexual consent, and the ways in which gender plays out in notions of acceptable and unacceptable intoxicated sexual encounters, we highlight how different levels of intoxication signal different sexual scripts. Narratives about sexual encounters at low levels of intoxication highlighted the role of intoxication in achieving sexual sociability, but they also relied on the notion that intoxicated consent was dependent on the social relationship between the partners outside drinking contexts. Narratives about sexual encounters in heavy drinking situations were more explicitly gendered, often in keeping with traditionally gendered sexual scripts. In general we found that when men discussed their own levels of intoxication, their narratives were more focused on sexual performance and low status sex partners, while women's and some men's narratives about women's levels of intoxication were focused on women's consent, safety, and respectability. Finally, some participants rely on "consent as a contract" and "intoxication parity"—the idea that potential sexual partners should be equally intoxicated—to handle relations of power in interpersonal sexual scripts. Since these notions are sometimes deployed strategically, we suggest that they may serve to "black-box" gendered inequalities in power between the parties involved.